Green Marketing Trek: Drivers, Challenges and Future Directions in Emerging Markets- A Systematic Literature Review - Muposhi, A. (Journal of Economics and Behavioral Studies, 2018)
Green marketing is growing in importance as it is tied to the universal goal of sustainable development. Although green marketing is gaining in prominence as a strategic imperative, mixed accounts a bound on its ability to create sustainable competitive advantage. Against this backdrop, this conceptual paper discusses the concept of green marketing, its drivers, challenges and future directions in the context of emerging markets. With the aid of a systematic literature review, this paper discusses market opportunities and challenges, implementation gaps, future directions and misconceptions associated with the adoption and implementation of green marketing. Results of literature review showed that the adoption of green marketing is driven principally by market opportunities, environmental legislation, operating efficiencies and improved profitability. Literature reviewed also notes challenges associated with green marketing implementation such as consumer cynicism, variability in demand of green products and exorbitant investment costs related to green technologies. This paper concludes that successful implementation of green marketing depends on a green vision that meticulously counterbalances the vested interests of key stakeholders in the value chain such as suppliers and customers. Effective green marketing implementation is also contingent on the ability of top management to integrate, coordinate and re-configure corporate competences to achieve green marketing goals. This paper recommends that marketers should resist the green marketing bandwagon but rather focus on understanding implementation imperatives that are preconditions for creation of sustainable competitive advantage. Marketers should also note that green marketing is not a panacea to all marketing challenges as it needs to be supported by sound marketing acumen